Targeted microbubbles carrying lipid-oil-nanodroplets for ultrasound-triggered delivery of the hydrophobic drug, combretastatin A4 - Charalambous, Antonia; Mico, Victoria; McVeigh, Laura E.; Marston, Gemma; Ingram, Nicola; Volpato, Milène; Peyman, Sally A.; McLaughlan, James R.; Wierzbicki, Antonia; Loadman, Paul M.; Bushby, Richard J.; Markham, Alexander F.; et al. (Nanomedicine, 2021)
The hydrophobicity of a drug can be a major challenge in its development and prevents the clinical translation of highly potent anti-cancer agents. We have used a lipid-based nanoemulsion termed Lipid-Oil-Nanodroplets (LONDs) for the encapsulation and in vivo delivery of the poorly bioavailable combretastatin A4 (CA4). Drug delivery with CA4 LONDs was assessed in a xenograft model of colorectal cancer. LC–MS/MS analysis revealed that CA4 LONDs, administered at a drug dose four times lower than drug control, achieved equivalent concentrations of CA4 intratumorally. We then attached CA4 LONDs to microbubbles (MBs) and targeted this construct to VEGFR2. A reduction in tumor perfusion was observed in CA4 LONDs-MBs treated tumors. A combination study with irinotecan demonstrated a greater reduction in tumor growth and perfusion (P = 0.01) compared to irinotecan alone. This study suggests that LONDs, either alone or attached to targeted MBs, have the potential to significantly enhance tumor-specific hydrophobic drug delivery. A number of highly potent and promising drugs fail to reach the clinic due to poor-water solubility. Lipid-stabilized Oil Nanodroplets (LONDs) were produced specifically for the encapsulation of poorly-water soluble drugs such as the vascular disruptive agent Combretastatin A4 (CA4). Initial pre-clinical work with CA4 LONDs showed an accumulation of CA4 in tumor tissue. Attachment of CA4 LONDs to VEGFR2-targeted Microbubbles (MBs) permitted the controlled and ultrasound triggered release of CA4 in tumors, confirmed by a reduction in tumor perfusion post-treatment. The combination of low dose irinotecan with CA4 LONDs-MBs further enhanced the anti-tumor effects of both compounds [Display omitted]